2020
DOI: 10.1136/jitc-2020-001072
|View full text |Cite
|
Sign up to set email alerts
|

Risk of HBV reactivation in patients with immune checkpoint inhibitor-treated unresectable hepatocellular carcinoma

Abstract: BackgroundImmunotherapy with immune checkpoint inhibitor (ICI) is a promising treatment for unresectable hepatocellular carcinoma (HCC). However, whether ICIs would have the risk of hepatitis B virus (HBV) reactivation and the necessary of nucleos(t)ide analogs (NUCs) prophylaxis are still unclear. We aimed to investigate the role of NUCs prophylaxis in HBV-infected patients who underwent ICIs treatment.MethodsThe study was a retrospective prospective design to review and follow-up consecutive 62 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 43 publications
3
70
0
1
Order By: Relevance
“…One out of six patients who did not receive NUCs treatment experienced HBV reactivation and was controlled by tenofovir treatment soon, no HBVrelated liver failure occurred. 40 Accordingly, HBV surface antigen (HBsAg), HBV core antibody (HBcAb), HBV surface antibody (HBsAb), and HCV antibody should be tested before ICI therapy. HBV DNA and quantitative HCV RNA levels and genotype should be obtained if HBsAg, HBcAb or HCV antibody are positive.…”
Section: Iraes In Patients With Hccmentioning
confidence: 99%
“…One out of six patients who did not receive NUCs treatment experienced HBV reactivation and was controlled by tenofovir treatment soon, no HBVrelated liver failure occurred. 40 Accordingly, HBV surface antigen (HBsAg), HBV core antibody (HBcAb), HBV surface antibody (HBsAb), and HCV antibody should be tested before ICI therapy. HBV DNA and quantitative HCV RNA levels and genotype should be obtained if HBsAg, HBcAb or HCV antibody are positive.…”
Section: Iraes In Patients With Hccmentioning
confidence: 99%
“…There was no increased incidence of major safety issues such as HBV reactivation during ICIs treatment. In a study of 60 CHB-HCC patients, no patients on antiviral therapy (regardless of HBV viral load at baseline) developed HBV reactivation, and one out of six not receiving Nucs had HBV reactivation [ 159 ]. In another large cohort of 397 patients, HBV reactivation only occurred in 2 HBsAg-positive patients (<1%) [ 160 ].…”
Section: Introductionmentioning
confidence: 99%
“… 22 A recent publication has also found that treatment with anti-PD-1 antibodies with simultaneous treatment with antiviral drugs is safe and precludes viral reactivation. 23 Indeed, general guidelines for immunosuppressed patients recommend antiviral prophylaxis for patients with occult HBV infection (HBsAg-negative, anti-HBc-positive, with detectable HBV DNA), 24 although the risk of reactivation is very low, 25 26 and that periodic monitoring of alanine aminotransferase levels, HBsAg and HBV DNA should be performed, with antiviral therapy deferred until confirmation of viral reactivation (seroconversion to HBsAg-positive or detectable HBV DNA). The most frequent antiviral drugs used for HBV are nucleoside or nucleotide analogs (NUCs), such as entecavir, tenofovir disoproxil or tenofovir alafenamide.…”
Section: Viral Hepatitismentioning
confidence: 99%